SNARE Proteins LjVAMP72a and LjVAMP72b Are Required for Root Symbiosis and Root Hair Formation in Lotus japonicus - Sogawa, Aoi; Yamazaki, Akihiro; Yamasaki, Hiroki; Komi, Misa; Manabe, Tomomi; Tajima, Shigeyuki; Hayashi, Makoto; Nomura, Mika (Frontiers in Plant Science, 2019)
SNARE (soluble N-ethyl maleimide sensitive factor attachment protein receptor) proteins mediate membrane trafficking in eukaryotic cells. Both LjVAMP72a and LjVAMP72b are members of R-SNARE and belong to a symbiotic subgroup of VAMP72 in Lotus japonicus. Their sequences are closely related and both were induced in the root upon rhizobial inoculation. The expression level of LjVAMP72a in the nodules was higher than in the leaves or roots; however, LjVMAP72b was expressed constitutively in the leaves, roots, and nodules. Immunoblot analysis showed that not only LjVAMP72a but also LjVAMP72b were accumulated in a symbiosome-enriched fraction, suggesting its localization in the symbiosome membrane during nodulation. Since there was 89% similarity between LjVAMP72a and LjVAMP72b, knockdown mutant by RNAi suppressed both genes. The suppression of both genes impaired root nodule symbiosis (RNS). The number of bacteroids and the nitrogen fixation activity were severely curtailed in the nodules formed on knockdown roots (RNAi-LjVAMP72a/72b). Arbuscular mycorrhization (AM) was also attenuated in knockdown roots, indicating that LjVAMP72a and LjVAMP72b were required to establish not only RNS but also AM. In addition, transgenic hairy roots of RNAi-LjVAMP72a/72b suppressed the elongation of root hairs without infections by rhizobia or arbuscular mycorrhizal fungi. Amino acid alignment showed the symbiotic subclade of VAMP72s containing LjVAMP72a and LjVAMP72b were a conserved six amino acid region (HHQAQD) within the SNARE motif. Taken together, our data suggested that LjVAMP72a and LjVAMP72b positively controlled both symbioses and root hair formation by affecting the secretory pathway.